A Modelling of Paraffin Shielding for BNCT Facility at Kartini Reactor Research using MCNPX - Hana Alfiani Lutfin (Indonesian Journal of Physics and Nuclear Applications, 2020)
The development of cancer in the world is very high. According to the World Health Organization (WHO) 1.69 million people die from cancer per year in the world, while the cases of cancer in Indonesia are also not much different. Some areas have a high prevalence of cancer, namely D.I Yogyakarta. Cancer has become a scourge for many people. There are many treatments available, such as chemotherapy, surgery, and radiation. Additionally, there is radiotherapy using neutron capture of boron-10 with energy 0.025 Ev. This treatment does not damage other tissue because the resulting particles such as He-4 and Lithium-7 have ranges that are a distance of 4.5-10 μm, so that the deposited energy is limited to the diameter of a single cell. The treatment is called Boron Neutron Capture Therapy (BNCT). There are several BNCT facilities such as a reactor, radial piercing beam port, thermal column, and shielding. The function of shielding is to absorb the neutron and alpha radiation. The shielding is made using paraffin material that is excellent in absorbing neutron radiation. In addition to paraffin there are also other materials, such as lead, used as paraffin casing. In a shielding simulation using MCNPX software, the resulting dose rate of radiation exposure outside of the BNCT facility in vitro and vivo tests is equal to 6.5 μSv / h. The thickness of the shielding paraffin used is 40 cm, Pb casing 25 cm, and 5 cm soft tissue.